Analysis of the trade position of China and the United States to understand the economic conflict - Contreras Álvarez, Isai; Molina-Vargas, Alejandro (Latin American Journal of Trade Policy, 2020)
This paper analyzes the trade position of China and the United States and the reason for the trade tensions between both economic powers. For this, trade position indicators are used and the logical method is applied, as well as comparative analysis and synthesis to understand the trade tensions, called in the academic literature as trade war. The study shows that the United States promotes free trade, as a strategy to increase or maintain its global participation, when the results favor it; on the other hand, when this does not occur or a threat is detected, as in the case of China, the United States uses trade policy instruments. The data shows that China has played well with the rules of WTO to increase its participation in the international trade since joining this organization.